METHODOLOGY FOR CONDUCTING COMMUNICATION MUSIC LESSONS IN PRESCHOOL EDUCATIONAL INSTITUTIONS - Ganiyeva Vazira Yusufovna (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
It is known that the combination of music, Fine Arts and literature provides great opportunities to reveal the spiritual horizons of art, introduces it as a language of communication between peoples, a memory of mankind, the thoughts, feelings, deeds and the present of people of the undo era have been preserved. Each teacher will be motivated to do research when drawing up a lesson plan. The article also analyzes the theoretical justification for the organization of integrated music classes in preschool educational organizations.